Limitations of Cs3Bi2I9 as lead-free photovoltaic absorber materials - Ghosh, Biplab (2020)
Lead (Pb) halide perovskites have attracted tremendous attention in recent years because of their rich optoelectronic properties, which have resulted in more than 22% power conversion efficient photovoltaics (PVs). Nevertheless, Pb-metal toxicity remains a huge hurdle for extensive applications of these compounds. Thus, alternative compounds with similar optoelectronic properties need to be developed. Bismuth possesses electronic structure similar to that of lead with the presence of ns2 electrons that exhibit rich structural variety as well as interesting optical and electronic properties. Herein, we critically assess Cs3Bi2I9 as a candidate for thin-film solar cell absorber. Despite a reasonable optical band gap (∼2 eV) and absorption coefficient, the power conversion efficiency of the Cs3Bi2I9 mesoscopic solar cells was found to be severely lacking, limited by the poor photocurrent density. The efficiency of the Cs3Bi2I9 solar cell can be slightly improved by changing the stoichiometry of the precursor solutions, which is most probably due to the reduction in nonradiative defects as evident from our single-crystal photoluminescence spectroscopy. However, detailed investigations on pristine Cs3Bi2I9 reveal that zero-dimensional molecular crystal structure remains one of the main bottlenecks in achieving high performance. On the basis of our comprehensive studies, we have proposed that a continuous network of three-dimensional crystal structure should be another major criterion in addition to proper band gap and suitable optical properties of the future PV compounds.